Development of an instrument-free and low-cost ELISA dot-blot test to detect antibodies against SARS-CoV-2 - Apú Navilla; Madrigal-Redondo Germán; Vega María Herrera; Corrales-Aguilar Eugenia; Segura-Ulate Ismael (Open Life Sciences, 2023)
Most laboratory tests to detect the presence of anti-SARS-CoV-2 antibodies use enzyme-linked immunosorbent assays (ELISA) or chemiluminescence immunoassays (CLIA); however, equipment for these immunoassays is unavailable in many areas of low- and middle-income countries. Rapid lateral flow immunoassay (LFIA) tests are an equipment-free option, but their high price may make them less suitable for conducting seroprevalence surveys. Here, we describe a simple dual antigen ELISA dot-blot test to detect anti-SARS-CoV-2 IgG antibodies with high sensitivity (94–98%) and specificity (92–100%), compared to commercially available ELISA and CLIA options. Additionally, this ELISA dot-blot test can be completed in one hour using minimal laboratory equipment. Importantly, this immunoassay is significantly more affordable than most LFIA tests available on the global market. The dot-blot strips may be stored for up to 7 days under freezing conditions. This ELISA dot-blot test is a cost-effective option for conducting seroprevalence screenings in areas lacking ELISA or CLIA facilities, compared to LFIA tests.